Sambat Online Program's Pursuit of Citizen-Centric Information Services Empowerment - Windah, Andi; Oktiani, Hestin; Nurhaida, Ida; Putra, Purwanto; Purnamayanti, Arnila; Maryani, Eri (CV. Literasi Indonesia, 2023)
The rise of digital technology has revived engagement between governments and citizens, advancing e-governance with improved communication, transparency, and flexibility. The Sambat Online Program promotes a citizen-centric approach to information services in Malang City which strategies for advancing e-governance in the digital age is considered important. This study aims to analyze challenges, strategies, and propose an actionable framework to improve Malang City's e-governance, with a focus on the Sambat Online Program’s pursuit of citizen-centric information excellence. This study used a qualitative case study approach to examine the program. The results show that the Sambat Online application in Malang City faces organizational challenges and social issues such as lack of leadership, resistance to change, digital divide, digital literacy, and social inclusion needs. Technological challenges occur in terms of cybersecurity, updates, and system scalability. It also found that the Malang City Government needs a user-oriented e-government approach to ensure data security and privacy. In other words, the platform makes it easy for users to submit complaints, increasing citizen involvement in improving public services, however continuous program assessment and improvement are essential. Areas for improvement include improved complaint management, digital training, and strengthened cybersecurity, with a focus on complaint management as the most effective solution. In conclusion, the program enhances communication and comprehension between governing bodies and the public, highlighting its significance in contemporary governance.